Lingue locali nella "Missio antiqua" (1645-1835) - Filesi, Teobaldo (L'Uomo società tradizione sviluppo, 2019)
The article surveys the studies of local languages carried out by Italian Capuchin missionaries sent to the Kingdom of Kongo an-d to Angola by the Sacra Con-gregationis de Propaganda Fide between 1645 and 1835. Italian missionaries were normally required to master Portuguese only, but many Capuchins managed to learn the local languages (despite considerable difficulties in codifying the Kikongo and Am-bu-ndu grammars) and use them in their Work With the natives. Kikongo and Ambundu grammars, as Well as diictionaries and catechisms, Were compiled and published between the' second half of the seventeenth century (Fr. Bonaventura da Sardegna) and the nineteenth century (Fr. Bernardo da Canicattì). These Works are extremely relevant to present-day studies.